-7-6n=7-4n

Simple and best practice solution for -7-6n=7-4n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7-6n=7-4n equation:


Simplifying
-7 + -6n = 7 + -4n

Solving
-7 + -6n = 7 + -4n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '4n' to each side of the equation.
-7 + -6n + 4n = 7 + -4n + 4n

Combine like terms: -6n + 4n = -2n
-7 + -2n = 7 + -4n + 4n

Combine like terms: -4n + 4n = 0
-7 + -2n = 7 + 0
-7 + -2n = 7

Add '7' to each side of the equation.
-7 + 7 + -2n = 7 + 7

Combine like terms: -7 + 7 = 0
0 + -2n = 7 + 7
-2n = 7 + 7

Combine like terms: 7 + 7 = 14
-2n = 14

Divide each side by '-2'.
n = -7

Simplifying
n = -7

See similar equations:

| (7x+4)+(5x+8)= | | .2x=61 | | -6-4p=4p-6p | | 2x(x+1)+12=18 | | X+2y+10=70 | | A(-3)+6(-4)= | | 0.15-7s=5.55 | | 2j-6=88 | | 0.15s+7=5.55 | | 0.80x+0.10(140)=0.40(31) | | 5c+3c+6-3=24 | | .30(-10000000)=1000000 | | 48k^2-6k=42 | | 6a+2a=-12+5a | | 4-3k=3+2k | | -4t^2+20t+1=0 | | -139=-x+3(-8+8x) | | 40p^2=-120+148p | | 7r-4(2r-8)=7r+3-(-7) | | v=-6+7v | | 7-k-2k=12 | | 4.56+19.5b=19.1b | | (4x+5)(5x-5)= | | 5x^2+160=-60x | | 5-2x+x=43 | | V-4=7v-10 | | 8x+2x+60+10x= | | 3p+0.75=5.88 | | 0=-16x^2+15x+5 | | y^2-20xy+100x^2=0 | | .3x+x=195 | | 3p-0.75=5.88 |

Equations solver categories